1980
DOI: 10.1111/j.1365-2141.1980.tb03809.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression and Serious Infections in Children with Acute Lymphoblastic Leukaemia:a Comparison of Three Chemotherapy Regimes

Abstract: Eighty-four children presenting with acute lymphoblastic leukaemia were entered into a trial designed to test the effect on host toxicity of regular drug-free periods during chemotherapy. Patients received the same total dose of drugs either continuously (daily), intermittently (a 5 d course every 3 weeks) or in an intermediate way between these two (a 14 d course followed by a 7 d gap). Mean neutrophil counts were lower in the intermittent group and fell significantly at 6 week intervals, after courses which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 7 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…cil Acute Lymphoblastic Leukaemia V Protocol (UKALL V) [3] in which remission induction with vincristine and prednisolone for four weeks with four doses of L-asparaginase during the third week is followed by prophylactic cranial irradiation (2,400 rads) and five intrathecal injections of methotrexate during the sixth to eighth week. The patients are then randomised to one of the three maintenance schedules which are shown in Fig parents gave informed consent for the liver biopsies, which were performed under general anaesthesia using the percutaneous technique with a modified Vim-Silverman needle.…”
Section: Methodsmentioning
confidence: 99%
“…cil Acute Lymphoblastic Leukaemia V Protocol (UKALL V) [3] in which remission induction with vincristine and prednisolone for four weeks with four doses of L-asparaginase during the third week is followed by prophylactic cranial irradiation (2,400 rads) and five intrathecal injections of methotrexate during the sixth to eighth week. The patients are then randomised to one of the three maintenance schedules which are shown in Fig parents gave informed consent for the liver biopsies, which were performed under general anaesthesia using the percutaneous technique with a modified Vim-Silverman needle.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary evidences from the literature suggested reduced rates of varicella and herpes zoster infections in children with ALL receiving intermittent 6-MP during maintenance therapy, with no effect on the event-free survival (EFS) rates. 9,10 This therapeutic strategy was further investigated by Koizumi et al 11 in the early 1980s. The Japanese Children's Cancer and Leukemia Study Group 5811 study enrolled 131 children with standard-risk ALL who were randomly assigned to receive maintenance treatment with either intermittent intravenous (IV) methotrexate (MTX) plus 6-MP, or the continuous use of oral 6-MP and weekly intramuscular (IM) MTX.…”
Section: Introductionmentioning
confidence: 98%
“…Only three relapses have occurred so far beyond six years, two of these in the seventh year. It is perhaps significant that two of these three very late relapses occurred in a group of children receiving intermittent maintenance chemotherapy in a pilot protocol for the national MRC UKALL V trial (Rapson et al, 1980) and that a number of late relapses have subsequently been observed in this trial (MRC 1986). While our study has the advantage of complete follow-up and the inclusion of all patients seen at a single centre, it does suffer from the disadvantage that the patients received a variety of treatments and that the likelihood of late relapse may vary according to therapeutic schedule.…”
Section: Discussionmentioning
confidence: 99%